ASEAN’s Cooperation on Labor Migration from 2007 to 2020: Practical Background and Reality - Mai Mai (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
The research is designed to understand the overall picture of workers migrating from one ASEAN’s country to another and incentives for ASEAN’s cooperation on labor migration in the period from 2007 to 2020. It also focuses on finding out the actual situation of this cooperation in the research timescale, shown in both policies and practical actions. Accordingly, this paper is expected to give an overview of labor migration in ASEAN and ASEAN’s efforts in helping this flow in the region as well as the lives of ASEAN’s citizens. The author used policy analysis method, document analysis and descriptive-historical approach as the main methodologies of the research. Received 24th July 2023; Revised 15th August 2023; Accepted 5th September 2023